2019
DOI: 10.3390/ijms20215278
|View full text |Cite
|
Sign up to set email alerts
|

Gender Related Changes in Gene Expression Induced by Valproic Acid in A Mouse Model of Autism and the Correction by S-adenosyl Methionine. Does It Explain the Gender Differences in Autistic Like Behavior?

Abstract: In previous studies we produced autism like behavioral changes in mice by Valproic acid (VPA) with significant differences between genders. S-adenosine methionine (SAM) prevented the autism like behavior in both genders. The expression of 770 genes of pathways involved in neurophysiology and neuropathology was studied in the prefrontal cortex of 60 days old male and female mice using the NanoString nCounter. In females, VPA induced statistically significant changes in the expression of 146 genes; 71 genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 134 publications
2
24
1
Order By: Relevance
“…Similar to our previous findings of sex-specific VPA-induced differences in gene expression in adult mice [46], we found that newborn mice prenatally treated with SAMe demonstrated significant sex differences in the expression of genes in the brain, thus the data were analyzed for males and for females separately. The full list of the genes with significant changes in their expression is detailed in the Supplementary Table S1 and Figure S1.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to our previous findings of sex-specific VPA-induced differences in gene expression in adult mice [46], we found that newborn mice prenatally treated with SAMe demonstrated significant sex differences in the expression of genes in the brain, thus the data were analyzed for males and for females separately. The full list of the genes with significant changes in their expression is detailed in the Supplementary Table S1 and Figure S1.…”
Section: Resultssupporting
confidence: 81%
“…We did not find any external malformations in the offspring in any of the groups. The weight gain of the offspring during the first 30 postnatal days was similar in all groups (Figure 1A-C) There were no differences in the developmental milestones between the control and SAMe-treated animals until the age of one month (Weinstein-Fudim L et al [46]).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Co-administration of VPA with SAMe normalized almost all gene expression changes produced by SAMe alone. Thus, an antagonistic action (interaction) between SAMe and VPA was demonstrated with prenatal treatment as well as with early postnatal treatment [131]. Interestingly, the main pathway affected by SAMe administration was the Vegfa (vascular endothelial growth factor a) pathway with 13 out of 26 genes significantly changed in males and 9 out of 26 genes in the Vegfa pathway changed in females.…”
Section: Effects Of Same and Vpa In Pregnancymentioning
confidence: 99%
“…This led to some clinical trials with minimal success [16]. VPA-induced autistic-like behavior in mice was prevented by concomitant administration of S-adenosyl methionine [17,18].…”
Section: Introductionmentioning
confidence: 99%